An Analysis of Social Dimension in Guillermo Del Toro's Pinocchio Film - Devitania, Devitania; Selli, Sastika; Syafitri, Dewi (EDULIA: English Education, Linguistic and Art Journal, 2024)
This research aimed to explain the social dimensions used by Pinocchio as the main character, which are found in Guillermo del Toro’s Pinocchio film. This research used a qualitative descriptive research design. The object of this research was Pinocchio in Guillermo del Toro’s Pinocchio film. The social dimension theory was used by Holmes (2013). The technique of data collection used was a documentation method. The procedure of data analysis was analyzed using three processes: data condensation, description, and conclusion. The results showed that there were 139 social dimensions consisting of 13 solidarity scales, 3 status scales, 62 formality scales, and 61 two functional scales used by the main character in Guillermo del Toro’s Pinocchio film. Therefore, it can be assumed that the formality scale is the one most widely used by the main character in this film. Students can improve their social skills and learn how to interact well with other people through learning social dimensions from the film. Keywords: Analysis, Film, Social Dimension